Properties of magnesium silicate hydrates (M-S-H). (January 2016) - Nied, Dominik; Enemark-Rasmussen, Kasper; L'Hopital, Emilie; Skibsted, Jørgen; Lothenbach, Barbara
Abstract: Investigations of synthetic magnesium silicate hydrate (M-S-H) samples have shown that M-S-H aged for 1 year can exhibit variable compositions with molar Mg/Si ratios in the range 0.7 ≤ Mg/Si ≤ 1.5. At lower Mg/Si ratio, additional silica is present whereas brucite is observed for Mg/Si ≥ 1.3. FT-IR and 29 Si NMR data reveal a high degree of silicate polymerisation, indicating the formation of silicate sheets. TGA shows the presence of bound water and of hydroxyl groups bound to Mg and as silanol groups in the M-S-H, in accord with 29 Si{ 1 H}CP/MAS and high-speed 1 H NMR measurements. Raman and XRD data suggest that the M-S-H structure is related to a disordered talc precursor at low Mg/Si and to a serpentine precursor at high Mg/Si ratio. Solubility products for M-S-H phases were calculated on basis of the compositions of the aqueous solutions and a solid solution model was suggested.